EFL TEACHERS' PEDAGOGICAL COMPETENCE IN THE CONTEXT OF ENGLISH CURRICULUM 2013: IMPLICATIONS FOR CLASSROOM ACTIVITIES - Budianto, Denis Era (2015)
Mastering pedagogical competence for teachers is an obligation for teachers (Kemendiknas, 2013). Therefore, this study focused on "EFL Teachers' Pedagogical Competence in the Context of English Curriculum 2013: Implications for Classroom Activities" in Bandar Lampung, Lampung. The research was conducted to investigate teachers' basic understanding, to figure out teachers' implementation, and to investigate problems faced by teachers in applying pedagogical competence in 2013 curriculum. This research was done because some teachers had not yet fulfilled the competence which can be seen from their lacknesses of preparation, of 2013 curriculum understanding, of implementation and of evaluation (Budi, 2014). The setting was in two targeted senior high schools in Bandar Lampung with one English teacher for each as the research participants. It was choosen by purposive sampling. In collecting the data, the research employed three instruments such as questionnaire, observation and documentation. It was found that teachers (1) had less understanding about the definition and the purpose of the 2013 curriculum, but good in mentioning the characteristics of pedagogical competence, (2) were good in implementing pedagogical competence, and (3) had seven problems in implementing pedagogical competence such as many qualifications in 2013 curriculum, few sources, different students' capabilities, no training discussed the purpose of 2013 curriculum, many details needed in making lesson plan, limited time in teaching, and the complicated in fulfilling the assessment. To conclude, teachers in Bandar Lampung implemented pedagogical competence in curriculum 2013 well. Keywords: English teacher, Teachers' pedagogical competence, 2013curriculum